Sacred Voters and Secular Elections:: Beyond Forming Consciences for Faithful Citizenship - Twiner, Joseph (Lumen et Vita, 2020)
As another major national election approaches, American Catholics need a better understanding of the political conscience. The United States Conference of Catholic Bishops’ document Forming Consciences for Faithful Citizenship (FCFC) attempts to provide guidance. However, the document has been roundly criticized by Catholics from various political persuasions. In attempting to understand political conscience today, it is helpful to return to the great thinkers of tradition, and in particular Thomas Aquinas. This paper aims at recovery of Thomas’ understanding of conscience, rooted in the act of synderesis and oriented towards the common good, as a fitting and critical interlocutor for FCFC.